Początki polskiej recepcji myśli Alexis de Tocqueville`a = Alexis de Tocqueville - the origins of Polish reception - Rakusa-Suszczewski, Mikołaj (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The present article is devoted to the original reception testimonies of A. de Tocqueville amongst Poles. The French thinker is portrayed here as an important intellectual figure for two main fractions of Polish immigration in the 19th century. Tocqueville inspired left wing activists of the Polish Democratic Society, as well as those affiliated to the rightwing Hotel Lambert.
Keywords: Tocqueville, Alexis Henri Charles Clérel de (1805-1859); socjologia; Francja; 19 w.